Answer:

Explanation:
Composition of two functions f(x) and g(x) is represented by,
(fog)(x) = f[g(x)]
If a function is,
f(x) = (-6x - 8)² [where x ≤
]
Another function is the inverse of f(x),

Now composite function of these functions will be,
![(fof^(-1))(x)=f[f^(-1)(x)]](https://img.qammunity.org/2021/formulas/mathematics/high-school/e8aeres1h3tm30daulsz101iuznizltf7q.png)
=
![[-6((√(x)+8)/(6))-8]^(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/qhykvypt5wilwesbg34046965i21risb6h.png)
=
![[-√(x)+8-8]^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/1q9w7bfe94sen1uuvulk0mmuipnliag0o9.png)
=

= x
Therefore,
